SURGICAL SITE INFECTION IN PATIENTS UNDERGOING ORTHOPEDIC SURGERY: AN INTEGRATIVE REVIEW STUDY - Silva, Adriana Paulo da (2023)
Infections at surgical sites related to orthopedic procedures are considered serious, as these surgeries generally involve the use of implant and prosthetic materials, thus increasing the risk of infection. In cases of severe SSI, the operated limb may need to be amputated or even lead to the patient's death. The objective of the article is to identify the risk factors associated with the development of surgical site infections in orthopedic surgeries and the main prevention strategies described in the scientific literature. The methodology used was an integrative literature review that was based on 11 scientific articles found in the LILACS, SCIELO and Virtual Health Library databases, published between 2013 and 2023. The results highlighted several risk factors associated with the development of SSI, including prolonged surgical time, advanced age, diabetes, obesity, emergency surgeries and length of stay. Proper use of Personal Protective Equipment (PPE), control of air contamination in the surgical environment, and education of both healthcare professionals and patients also play crucial roles in preventing infections at surgical sites. The complexity of the SSI prevention scenario involves specific characteristics of patients, the hospital environment and interconnected institutional protocols. Continued research, longitudinal studies, and collaboration between multidisciplinary teams are critical to improving the quality of care and reducing the occurrence of SSI in orthopedic surgeries. Nurses play a significant role in implementing prevention strategies and overseeing adherence to guidelines, making research and ongoing updating crucial to successful SSI prevention in this context.